An ulcer on the arm of an immunocompromised patient. - Hasbún Zegpi, M.T.; Alfaro-Sepúlveda, D.; González Bombardiere, S. (European Journal of Pediatric Dermatology, 2020)
Primary cutaneous aspergillosis is an uncommon entity. It may occur in immunosuppressed hosts or in patients with a cutaneous barrier disruption. It requires a direct inoculation of the fungus, which usually occurs through contaminated medical devices. The infection spreads locally. It is clinically characterized by macules, papules, plaques or hemorrhagic blisters, which may progress into necrotic ulcers. We reported the case of an 18-year-old male, diagnosed with refractory acute lymphoblastic leukemia, who developed a necrotic ulcer at the site of an intravenous catheter.